THE DETERMINANTS OF AGRICULTURAL EXPORTS: EMPIRICAL VALIDATION FOR THE CASE OF TUNISIA - Sayef Bakari; Sirine Khalfallah; Ahmed Zidi (International Journal of Food and Agricultural Economics, 2021)
In this investigation, we attempt to identify and to examine the determinants of agricultural exports in Tunisia. To achieve this aim, we used annual data for the period 1972 – 2017 and seven ad hoc specifications. Empirical results of each specification show us that gross domestic product in the agricultural sector, agricultural imports, bank loans to the agricultural sector and imports of agricultural machinery have a positive effect on agricultural exports in the long run. Conversely, domestic investments in the agricultural sector and the exploitation of agricultural land have a negative effect on agricultural exports in the long term. In the short term, only domestic investments in the agricultural sector cause agricultural exports. Findings and interpretations provide evidence that is very substantial to inspire validity planning and reforms to ameliorate agricultural investment and agricultural trade, so it can uphold economic development in Tunisia.